KEBIJAKAN PENYELENGGARAAN PENYULUHAN PERTANIAN DI ERA OTONOMI DAERAH DI KABUPATEN SLEMAN PROPINSI D.I. YOGYAKARTA - Husodo, Sapto; Arifin, Miftakhul (Jurnal Ilmu-Ilmu Pertanian, 2009)
Regional autonomy policy has resulted in changes in policy direction in all sectors including the agricultural sector, particularly regarding the implementation of agricultural extension. This study aimed to elucidate the process of policy implementation of agricultural extension, the stages of preparation, and the factors that influence the policy-maker in the preparation of the implementation of agricultural extension policy in the era of regional autonomy. This research is also intended to identify forms of organization of agricultural extension policy after the era of regional autonomy, which involves institutional level of Extension Center for Agriculture, Fisheries and Forestry. The study was conducted since September until December 2009 in Sleman Yogtakarta Special Province by using qualitative descriptive methods. From the research we can conclude the process of policy making in the early era of regional autonomy in Sleman regency have not involving related parties escara real, but beginning in 2009 has involved the role of agricultural extension, although not proportionally. Factors that influence policymakers in the formulation of policies covering internal and external factors. Internal factors including the interest, courage, professionalism, and the limits of authority, while external factors include the existence of social forces and public policy. Among these factors occur attraction to dominate in the policy making process. The form of policies relating to financing, institutional and human resources quite different to the rules specified national regulation. The implementation of agricultural extension realization that is based on local government policy on decentralization era have ups and downs.